An introduction to managing people in organizations - Pitsis, Tyrone (Henry Stewart Talks, 2010)
Overview, Shifting emphasis, Orientation, Reality in management?, The nature of management, Managing people, The brain metaphor, Uncertainty, Perception, Perceptual errors, Affective forecasting, Key pointers, Managing perceptual errors, Positive psychology, Learned helplessness, Helplessness vs. helpfulness, Application (appreciative inquiry), 24 core strengths, Strengths psychology